Rule of Law in Han Feizi's Thought - Shokrani, Maziyar (Advances in Social Sciences Research Journal, 2018)
In this paper, the author will review the meaning of the rule of law and investigate the Chinese major political theorist of the pre-Qin period, Han Feizi, thoughts on legalism and examine whether his philosophy is in conformity with contemporary concept of the rule of law. The paper concludes that considering the knowledge and progress of Han’s era, we may see his philosophy as one that promotes rule of law.